SUBSTRATE TEMPERATURE EFFECT ON ELECTRICAL PROPERTIES THIN LAYER SEMICONDUCTOR PbS, PbSe AND PbTe PREPARED BY VACUUM EVAPORATION TECHNIQUE - abdul mafahir iim; sutjitno tjipto; Ariswan Ariswan (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2016)
This research aims to produce a thin layer of semiconductor with PbS, PbSe and PbTe material  by vacuum evaporation  techniques and  to find out electrical properties of these materials. Thin layer was produced  by using vacuum evaporation  techniques. Varied  temperature of substrate is used as  parameters during  preparation,ie  without heating (sample 1), 200 ℃ (sample 2), 350 ℃ (sample 3), and 500 ℃ (sample 4). Electrical properties are characterized by  using a four point probe (FPP). Results showed that  this  thin layer of PbS, PbSe and PbTe  is  type N semiconductor with  resistivity in   Ω.cm to  Ω.cm oreder Keywords: thin layer, evaporation, electrical properties